The effects of cause-related marketing on consumer repurchase intentions through brand resonance: Moderating effects of news articles and advertising - Usman Ahmad Qadri; Alsadig Mohamed Ahmed Moustafa; Mazuri Abd Ghani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
The increasing reliance on news articles and advertising to communicate cause-related marketing (CRM) initiatives highlights a critical gap in understanding their effects on brand equity, especially post-natural disasters. This study investigates the role of brand resonance as a mediator and media coverage (news articles and advertising via newspapers) as a moderator in the relationship between CRM and consumer repurchase intention (CRI). Despite widespread discussions about the impact of paid media on brand equity, the intricate interactions between CRM message framing, the medium of dissemination, and their collective influence on brand resonance during crises still need to be fully explored. Utilizing attribution theory and signaling theory, this research aims to bridge these gaps by examining how different media types affect the effectiveness of CRM activities. This study used an accidental sampling technique to collect data from 410 respondents and applied PROCESS Macro v4.0 to test the research hypotheses. The findings extend the existing literature by providing empirical evidence on how CRM, when mediated by brand resonance and moderated by media coverage, shapes corporate reputation. This research not only deepens the theoretical understanding but also offers practical insights for optimizing media strategies to enhance brand resonance and consumer satisfaction in the aftermath of natural disasters.
Keywords: 330; Cause-related marketing; brand resonance; consumer repurchase intention; news articles; advertising; natural disasters